Getting started with IBM Hyper Protect Data Controller - White, Bill; Coulson, Andy; Hoareau, Guillaume; Katonica, Jason; Panting, Roy; Richard, Philippe; Weiss, Maxwell; Yan, Eva (IBM Redbooks, 2022)
IBM® Hyper Protect Data Controller is designed to provide privacy protection of your sensitive data and give ease of control and auditability. It can manage how data is shared securely through a central control. Hyper Protect Data Controller can protect data wherever it goes--security policies are kept and honored whenever the data is accessed and future data access can be revoked even after data leaves the system of record. This IBM Redbooks® publication can assist you with determining how to get started with IBM Hyper Protect Data Controller through a use case approach. It will help you plan for, install, tailor and configure the Hyper Protect Data Controller. It includes information about the following topics: Concepts and reference architecture Common use cases with implementation guidance and advice Implementation and policy examples Typical operational tasks for creating policies and preparing for audits Monitoring user activity and events This IBM Redbooks publication is written for IT Managers, IT Architects, Security Administrators, data owners, and data consumers.
Online resource; Title from title page (viewed January 4, 2022)
Keywords: Computer networks -- Security measures; Computer security; Cloud computing -- Security measures; Computer Security; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; Infonuagique; Sécurité; Mesures; Computer networks; Security measures